„Ze stanowiska katolickiego”. Ks. Józefa Kobylińskiego koncepcja totalizmu państwowego - Dubel, Lech (Wydawnictwo Uniwersytetu Wrocławskiego, 2011)
According to Józef Kobyliński, the essential and obvious features of totalism include: 1. The State is recognized to be the highest aim. 2. The race may also be the State’s highest aim Germany. 3. The monopoly of will by way of complete subordination and blind obedience occurs in the State. 4. The total State is principally atheistic. 5. It is a one-party system. 6. Universalism, commonplaceness of behaviour and absence of any initiative prevail here. According to the author, the basic feature of the total State is its attempt at total predominance over individuals and social groups. Militarism and economic imperialism over neighbors are resorted to whenever possible. Totalitarianism is basically about annihilating anything that could oppose the State and limit its lawlessness. In the totalitarian State the individualism of democracy is ousted by universalism.
Keywords: Kobyliński, Józef; totalitaryzm; katolicyzm